Pembuatan Sistem Informasi Transportasi Umum di Kota Surakarta dengan Framework Sencha Touch - Ramos Somya; Feldy Judah Kambey (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2015)
Transportation has important role in a country to support the economy. The lack of information about public transportation in a city causes some problems that must be faced by citizens. Some of this problems are: the citizens do not know the route of public transportation, they have to come to the station to check the train schedules, and they do not know the phone number of the taxi when they need it. This study aims to provide public transportation information system to solve that problems. The public transportation information system is built in multi platform mobile with HTML5 and Sencha Touch framework. Sencha Touch is used to build mobile application that able to run in some mobile platforms using PhoneGap technology. In addition, Sencha Touch has better graphics than other frameworks. The public transportation information system in this study helps the citizens to find the information about public transportation in Surakarta. This application runs in some mobile platforms, such as Android, Blackberry, iOS and Windows Phone.